(untitled) (Annual Transactions of the Nordic Rheology Society, 2024)
Based on many years of work with the calculation of dynamic temperature of drilling fl uids during operations, a pedagogic overview of how the calculation of heat transfer and temperature is closely linked with fl uid flow properties will be given. For example, the onset of vortices and turbulence due to imposed flow and rotation of the drill string / running string has a large impact on heat transfer. Changing from idealized laminar flow with only conduction radially to flow with vortices and turbulence with convective heat transfer also radially, causes a large boost of heat transfer, especially along the outer wall of the drill string. Clearly, the rheological behaviour of the fluid is essential. Different vibrational modes and other disturbances add to the complexity of the picture, such that some effects can be modelled from fi rst principles, while others are too complicated for practical models and must be handled differently.